Stay : the true story of ten dogs - Muntean, Michaela; Bailey, K. C; Kazmierski, Stephen (New York : Scholastic Press, 2012)
Luciano Anastasini, a man who calls the circus home, and ten homeless dogs are brought together by fate.
School Library Journal, March 2012
Publisher's Weekly, February 2012
Kirkus Review, February 2012
5.0
3-6
Keywords: Dog adoption -- Juvenile literature; Anastasini, Luciano -- Juvenile literature; Circus performers -- Juvenile literature; Dogs -- Behavior -- Juvenile literature; Dog adoption; Anastasini, Luciano; Circus performers; Dogs -- Behavior; Dog adoption; Anastasini, Luciano; Circus performers; Dogs -- Behavior